Census of India 2001 and After - ASHISH BOSE (Economic and Political Weekly May 19, 2001, 2001)
It goes to the credit of the 2001 Census Commissioner that he could at once see a shocking aspect of this Census, namely, a sharp decline in the female-male ratio in several states. Migration cannot explain this phenomenon which must be the consequence of female foeticide on a massive scale, if not female infanticide and higher female child mortality rates. It is unfortunate that even in the progressive south Indian states, except Kerala, the child sex ratio has declined.